Library user education program 1993/1994 - Devindar, K.C. (Perpustakaan Universiti Malaya, 1993)
In conjunction with the Orientation Week organised by the Student Affairs Division of the University of Malaya, the Library undertook a Library User Education Programme for new students of the 1993/94 academic session. With the objective of inculcating lifelong skills and encouragement of independent learning the user education programme that lasted for a month was drawn up incorporating library orientation and the more indepth library instruction. During the library tour students were introduced to the library, its collection and services. OPAC sessions were conducted to instruct students on information retrieval to meet their needs. Follow-up sessions for more indepth searching was facilitated and a reference enquiry desk service was set up. In future the Library will playa more determining role in the University's orientation programme to further improve the effectiveness of user education.